Invasion risks and social interest of non-native woody plants in urban parks of mainland Spain - Álvaro Bayón; Oscar Godoy; Montserrat Vilà (Anales del Jardín Botánico de Madrid, 2022)
Urban parks and gardens are one of the most important pathways for the deliberate introduction of non-native plant species, some of which cause environmental and socioeconomic impacts. We conducted a risk assessment on 388 non-native woody plant species from 46 urban parks of mainland Spain to classify them in lists based on their invasion status, being invasive elsewhere, climate matching with the area of origin, and potential to cause negative impacts. Only Ficus benjamina has no potential to invade (Green list). Four species are invasive and regulated (Priority list); 47 invasive or potentially invasive species can cause more impact types than the median value (Attention list), while 12 can cause less impacts than the median (Watch list). There is no park without any invasive or potentially invasive species. The most common potential impacts could be competition with native species (80% species) and the physical modification of the habitats (71%). We also identified 31 species with potential to cause human health impacts. Some species could cause several impact types. The most correlated potential impacts are among competition, toxicity, and alteration of natural succession and habitat structure. The most frequently planted invasive and potentially invasive species are the ones with the largest standard trending value from Google Trends, and therefore the ones with more societal interest.